Elevated Peripheral Brain-Derived Neurotrophic Factor Level Associated With Decreasing Insulin Secretion May Forecast Memory Dysfunction in Patients With Long-Term Type 2 Diabetes - Huang, Xi; Xie, Zuolin; Wang, Chenchen; Wang, Shaohua (Frontiers in Physiology, 2022)
Background: With the progressive course of diabetes and the decline of islet function, the cognitive dysfunction of patients aggravated. Objective: We aimed to investigate the roles of brain-derived neurotrophic factor (BDNF) and the Val66Met polymorphism in mild cognitive impairment (MCI) in patients with type 2 diabetes mellitus (T2DM). Methods: A total of 169 Chinese patients with T2DM were recruited and divided into long-term (diabetes duration >10 years) and short-term (diabetes duration ≤10 years) diabetes, and in each group the patients were separated as MCI and the control. Demographic characteristics, clinical variables, and cognitive performances were assessed. The plasma BDNF level was measured via enzyme-linked immunosorbent assay. The Val66Met polymorphisms were analyzed. Results: Long-term T2DM have lower 2 hours postprandial C-peptide (p<0.05). BDNF level in patients with MCI was slightly higher than that in the controls in each duration group without statistically significance. The relationship of BDNF to Montreal Cognitive Assessment was not proven either. However, in the long-term diabetes group, BDNF concentration remained as an independent factor of logical memory test (β=-0.27; p<0.05), and they were negatively correlated (r=-0.267; p=0.022); BDNF was also negatively correlated with fasting C-peptide (r=-0.260; p=0.022), 2 hours postprandial C-peptide (r=-0.251; p=0.028), and homeostasis model assessment of insulin resistance (r=-0.312; p=0.006). In genotypic groups, BDNF Val/Val performed better in logical memory test than Met/Met and Val/Met. Conclusion: Elevated peripheral BDNF level associated with declined islet function, when combined with its Val66Met polymorphism, may forecast memory dysfunction in patients with long-term T2DM.